The relationship between on-the-job training and work performance at MMC Oil and Gas Engineering Sdn Bhd (MMCOG) Jalan Tun Razak, Kuala Lumpur / Siti Aisah Hashim - Hashim, Siti Aisah (2014)
Research has found that the on - the - job training were partially successfully in realizing the training goals and also in the immediate effect explanation training was satisfactory (Klink M. & Streumer J. 2002). This study reports the relationship between on- the-job training and work performance among employees at MMC Oil and Gas Engineering Sdn Bhd (MMCOG) Jalan Tun Razak Kuala Lumpur. Many organizations and learning institutions in Malaysia have implemented on the job training because of its effectiveness as a training approach. However, studies have shown that employees are apprehensive about the types of training that relate to their work performance in their career. The theoretical framework for this study is based on conceptual framework. Two dimensions representing de1t variables that contribute to the work performance which is on-the-job training. Data are gathered through surveys among the employees in the MMCOG which implemented on - the - job training. Among the dimension which influenced the level of effectiveness of on - the job training are coaching and internship. Findings from this study provided insights on the attitude, employees towards the level of effectiveness of on the job training. Its practical contribution includes other types of on - the job training and psychological trainers which can be incorporated into the on the -job training program to address the improvement of low effectiveness on the job training dimension which are coaching and internship.